DIVERSIFICATION OF FINANCIAL SOURCES AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF CIVIL SOCIETY INSTITUTIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Civil society institutions are increasingly involved in solving social problems, protecting public interests and delivering community-based initiatives. Their sustainability depends on financial resources, but the quality of those resources is as important as their volume. A civil society institution may receive a considerable amount of funding in a given year and still remain financially vulnerable if the funding is temporary, concentrated in one donor, or restricted to a narrow project. Therefore, diversification of financial sources becomes one of the key factors of sustainable development.